Peran peer educator dalam upaya peningkatan imunitas tubuh remajadi masa pandemi COVID melalui penyuluhan gizi seimbang - Fatmalina Febry; Ainy, Asmaripa; Etrawati, Fenny (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Implementation of Balanced Nutrition is critical to dealing with the COVID-19 pandemic. It is hoped that adolescents can apply balanced nutrition in the current situation so that the body remains healthy and increases body immunity. The purpose of this activity is to increase adolescent knowledge about the Application of Balanced Nutrition to support immunity during the Covid 19 pandemic through peer educator empowerment. The target of this activity is the youth of SMPIT Bina Ilmi Palembang which consists of 5 peer educators and 38 adolescent participants. This activity consists of two stages, namely peer educator training and nutrition counseling to adolescents by peer educators. Peer educators were selected by the school and then given training on balanced nutrition and its relationship to body immunity through Zoom meetings. Then peer educators provide counseling using the lecture method with PowerPoint tools to adolescents simultaneously through the breakout room at the Zoom meeting and conduct pretest and postest using Google form through WhatsApp group. The result of this activity is an increase in knowledge of both nutrition ambassadors and adolescents after receiving training. It is necessary to carry out regular training on balanced nutrition and body immunity so that adolescent knowledge is getting better so that it can improve the adolescent's immune system.